“The Death of Medicine as an Art of Humanity”. Multi-Level Ethical Implications of Integrating Mortality Prediction Algorithms in End-of-Life Care - Brake, Jad; Newton-Mari, Kelly; Virani, Alice; Ho, Anita (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Artificial intelligence-powered mortality predictive algorithms (MPAs) have been developed to predict a patient’s life expectancy, with the hope that algorithmic outputs will help providers to find an optimal time to initiate end-of-life (EoL) conversations to enhance goal-concordant care. This qualitative research, conducted in British Columbia (BC), Canada, examines health care providers’ perspectives on ethical implications of using AI-powered MPAs in EoL care. This paper discusses how MPAs raise familiar but also new multi-level ethical issues regarding the use of predictive analytics in clinical medicine. These ethical concerns and considerations span four levels: individual, professional, organizational, and societal. Our analysis of these interconnected levels reveals three key and overlapping insights: 1) the need to redefine clinicians’ roles within a changing techno-therapeutic landscape; 2) the challenge of navigating EoL hope in the context of emerging predictive tools; and 3) the importance of fostering a balanced and holistic approach to EoL care amid rapid advances in AI. By uncovering the complexity of ethical implications of using MPAs in the sensitive and vulnerable context of the final stages of a person’s life, this work provides a multi-level framework that can inform best practices. It also underscores a holistic view of care and stresses the need for ethical frameworks, guidelines, interdisciplinary collaboration and education to inform the design and implementation of MPAs in EoL care.